Development Of Vertebrate Diversity Comics In The Gunung Puntang Area As A Learning Medium - Abdullah Saepul Anhar; Sumiyati Sa'adah; Mar'atus Sholikha (Riviera Publishing, 2024)
Visual media - based education is an innovative strategy For increase interest Study student to material complex , including diversity life . One of effort For support learning This is through development comic education based on local . Research This focused on development comic education about vertebrate diversity in the region Mountain The Puntland as an innovative, interesting and relevant learning media. Research This use Research and Development (R&D) method with 3-D model stages (Define, Design, Develop). Qualitative data collected through interview with teachers and experts For identify learning media needs, while quantitative data obtained from validation products by experts materials, media experts, and teachers, as well as readability tests by students. Research result show that comic this is valid and effective as a learning medium. Validation expert material to obtain average score 88%, validation media expert 83%, and science teacher validation 86%, all of which including in very valid category. Readability test by students show average score of 88%, with media aspects reach mark highest by 94%. This comic rated capable interesting attention students, improve understanding to material diversity life, and grow awareness will importance conservation diversity local life. Study This give implications significant in development teaching materials based on local. This comic No only can used as a learning medium but also as tool For increase awareness student will importance preservation environment. With thus, comics This potential become a learning medium supporting alternatives? achievement objective education national.